Finding the right personal representative to the deceased in estate administration: expounding the Malaysian Legal considerations - Mohd Noor, Nor Azlina; Halim, Akmal Hidayah (The CLJ Legal Network Sdn Bhd, 2016)
Personal representation is a noblest obligation in the deceased’s estate administration. The person appointed as personal representative is entrusted with the highest degree of honesty and good faith in discharging his statutory obligations. They have sworn vide the grant letter of representation that they will solemnly and faithfully administer the deceased’s estate and to render a just and true account relating to the estate administration. The question to be considered is who would be the capable and illegible person to be appointed as personal representative? This question is relevant as the law vests enormous powers to the personal representative and therefore putting the estate beneficiaries in the danger of being victimise by abusive acts of dishonest personal representative. Therefore the act of appointing a right personal representative is a necessity in the estate administration. Hence this paper seeks to examine the Court’s tendency in the appointment of personal representative in order to protect the interest of estate’s beneficiaries. For this purpose, the paper analyses relevant statutory provisions as provided by Probate and Administration Act 1959. An analysis of the decided cases is also made to identify the requirement given by law in choosing the personal representative. This paper concludes that there is no hard and fast rule pertaining to the requirement of law in choosing a personal representative to the deceased’s estate. With the exclusion of a minor and unsound mind, any other person can be appointed as personal representative. What matter most is after being appointed as personal representative, they must carry out their job carefully and judiciously in which any failure to properly do so may give right to the estate beneficiaries to take legal action against them.